2016
DOI: 10.1016/j.krcp.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the probability of survival in acute paraquat poisoning

Abstract: BackgroundParaquat (PQ) concentration–time data have been used to predict prognosis for 3 decades. The aim of this study was to find a more accurate method to predict the probability of survival.MethodsThis study included 788 patients with PQ poisoning who were diagnosed using plasma PQ concentration between January 2005 and August 2012. We divided these patients into 2 groups (survivors vs. nonsurvivors), compared their clinical characteristics, and analyzed the predictors of survival.ResultsThe mean age of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
2
8
3
Order By: Relevance
“…1a and Supplementary Results , Supplementary Fig. 1a ) and is similar to the plasma concentration observed in patients with acute PQ toxicity [ 11 , 19 ]. Human Jurkat T-acute lymphoblastic leukemia cells were transduced with a metabolic single guide RNA (sgRNA) library containing ~10 unique sgRNAs for each of the ~3,000 metabolic genes (~30,000 sgRNAs total) [ 20 ] and cultured in the presence or absence of 110 μM PQ for at least 10 days ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 77%
“…1a and Supplementary Results , Supplementary Fig. 1a ) and is similar to the plasma concentration observed in patients with acute PQ toxicity [ 11 , 19 ]. Human Jurkat T-acute lymphoblastic leukemia cells were transduced with a metabolic single guide RNA (sgRNA) library containing ~10 unique sgRNAs for each of the ~3,000 metabolic genes (~30,000 sgRNAs total) [ 20 ] and cultured in the presence or absence of 110 μM PQ for at least 10 days ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 77%
“…During this process, WBC, cytokines, and other inflammatory factors are produced, leading to acute lung injury and multi-organ dysfunction. Higher WBC count is associated with negative patient outcomes (Sun et al, 2016). We also found that WBC count at the time of admission was higher in the mortality group than that in the survival group in our study (p < 0.01).…”
Section: Discussionsupporting
confidence: 68%
“…However, PQ can directly attack the renal tubules, leading to renal damage or acute failure. This reduces PQ excretion, which causes an accumulation of PQ in the tissues and organs and increases body damage (Molck and Friis, 1998;Sun et al, 2016). Urea nitrogen and serum Cr levels increase during this process.…”
Section: Discussionmentioning
confidence: 99%
“…We found 5 articles with a total of 1311 patients. [3839404142] Eight hundred and thirty-seven patients were underwent HP, of which 592 patients died (70.72%). Four hundred and seventy-four patients did not receive HP, of which 428 patients died (90.29%).…”
Section: Resultsmentioning
confidence: 99%